Government Immunity and Liability in Tort: The Case of Covid-19 Pandemic’s Management in Indonesia - Susanti, Laras (Kertha Patrika; Vol 43 No 2 (2021), 2021)
The Covid-19 pandemic has cost human lives and threaten the world’s economy. Responding to this unprecedented history, governments are expected to take both public health and economic recovery actions. This article conveys analysis on how Indonesian courts might examine government tort cases on the government’s liability in handling the pandemic. A normative juridical method is used to analyze primary and secondary legal sources. The writer finds that with the enactment of Law Number 30 of 2014 on Government Administration, a government concrete action is also an object to suing government before the state administrative court. Furthermore, the recent Supreme Court Regulation Number 2 of 2019 on Guidance Dispute Settlement Mechanism of Government Action and Competence to Adjudicate Government Tort governs that the state administrative court is the only court that has competence over government tort. As a result, claims of government tort submitted to the general court must be dismissed. In fact, this recent development created confusion on the side of justice seekers and judges as well that might affect the outcome of Covid-19 government tort claims. Studying previous government tort cases and focusing its exploration on the development of government immunity and liability, this article finds that Indonesian courts use Article 1365 Civil Code equipped with laws and regulations in administrative governance and specific fields legal frameworks to examine government tort cases. Even though such laws may state that the government may not be sued, the courts may use the Constitution of 1945 to establish a right to sue. During the Covid-19 pandemic, laws and regulations related to disaster and public health management along with the public interest principle must be examined to determine government tort.